Precision targeting of the plasminogen activator inhibitor‐1 mechanism increases efficacy of fibrinolytic therapy in empyema. Issue 9 (15th May 2021) - Florova, Galina; Girard, René A.; Azghani, Ali O.; Sarva, Krishna; Buchanan, Ann; Karandashova, Sophia; DeVera, Christian J.; Morris, Danna; Chamiso, Mignote; Koenig, Kathleen; Cines, Douglas B.; Idell, Steven; et al.
Abstract: Plasminogen activator inhibitor‐1 (PAI‐1) is an endogenous irreversible inhibitor of tissue‐type (tPA) and urokinase (uPA) plasminogen activators. PAI‐1‐targeted fibrinolytic therapy (PAI‐1‐TFT) is designed to decrease the therapeutic dose of tPA and uPA, attenuating the risk of bleeding and other complications. Docking site peptide (DSP) mimics the part of the PAI‐1 reactive center loop that interacts with plasminogen activators, thereby affecting the PAI‐1 mechanism. We used DSP for PAI‐1‐TFT in two rabbit models: chemically induced pleural injury and Streptococcus pneumoniae induced empyema. These models feature different levels of inflammation and PAI‐1 expression. PAI‐1‐TFT with DSP (2.0 mg/kg) converted ineffective doses of single chain (sc) tPA (72.5 µg/kg) and scuPA (62.5 µg/kg) into effective ones in chemically induced pleural injury. DSP (2.0 mg/kg) was ineffective in S . pneumoniae empyema, where the level of PAI‐1 is an order of magnitude higher. DSP dose escalation to 8.0 mg/kg resulted in effective PAI‐1‐TFT with 0.25 mg/kg sctPA (1/8th of the effective dose of sctPA alone) in empyema. There was no increase in the efficacy of scuPA. PAI‐1‐TFT with DSP increases the efficacy of fibrinolytic therapy up to 8‐fold in chemically induced (sctPA and scuPA) and infectious (sctPA) pleural injury in rabbits. PAI‐1 is a valid molecular target in our model of S . pneumoniae empyema in rabbits, which closely recapitulates key characteristics of empyema in humans. Low‐dose PAI‐1‐TFT is a novel interventional strategy that offers the potential to improve fibrinolytic therapy for empyema in clinical practice. Abstract : Empyema remains an important clinical problem with high mortality among patients 65 years and older. Targeting plasminogen activator inhibitor 1 (PAI‐1) in two rabbit models of pleural injury resulted in to up to eight‐fold increases in the efficacy of fibrinolytic therapy (decrease in dose needed for effective treatment). Low‐dose PAI‐1‐targeting fibrinolytic therapy would expand the population of patients that could benefit from treatment and improve therapeutic outcomes.